Fabrication of Co–Cr–Mo endoprosthetic ankle devices by means of Selective Laser Melting (SLM). (15th September 2016) - Liverani, E.; Fortunato, A.; Leardini, A.; Belvedere, C.; Siegler, S.; Ceschini, L.; Ascari, A.
Abstract: A study of Cobalt–Chromium–Molybdenum endoprosthetic ankle implant fabrication by means of SLM is presented, including process characterization and kinematic considerations. Process optimization is first performed on samples with simple geometry to maximize density and mechanical strength using Co–Cr–Mo powders. Parameters such as laser scanning velocity, laser power and scanning strategy are varied, amongst others. Mechanical tests and microstructural analyses are performed to define process parameter windows for fabrication of near full density prostheses with negligible microstructural defects. Prosthetic ankles, based on medical imaging and biomechanical modeling, are then manufactured and kinematically tested to confirm their functional integrity and performance. Graphical abstract: Highlights: The first part of the present paper is devoted to identifying the optimal process window for manufacturing of CoCr SLM; SLM CoCr prototypes were then produced, exploiting the previously determined optimal process parameters; The SLM ankles were kinematically tested in order to assess the joint's ability to replicate natural joint motion.